Analysis of the Effect of Social Media on the Marketing Process in a Store or Business Entity "Social Media Store" - Indriyani, Indriyani; Dewanti, Paula (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The world has been affected by the global recession so they have developed crisis strategies and are looking for new tactics to face this global challenge. While businesses are looking for new tactics, reaching out and understanding the many things and possible changes in their attitudes and behavior due to the crisis has become important for companies during and after this economic downturn. Recently, one of the most striking tools that companies use to achieve their goals is social media, by all means. This study aims to examine the effect of social media on the marketing process in a store or business entity by means of literature articles and books on effectiveness. Social media marketing, where the result is that social media is very influential in increasing traffic on business websites and increasing business turnover. The "Sosmed Store" business entity has a target market, namely entrepreneurs who want their business to be known more quickly by the public through the internet. The products offered by the "Sosmed Store" can also develop according to the needs of the intended target market. The products offered do not ask for personal information at all to users and potential users. Because it does not store important data from its users, the products offered are getting less and less attacked.